Bahamas : economic report (World Bank Washington, D.C.US, 1986)
Reviews performance of the Bahamas economy in the early 1980's. Examines performance of individual sectors, issues that affect them and strategies for their development. These sectors include inter alia, tourism, offshore banking, health and education. Discusses economic challenges that face the economy viz. external vulnerability deriving from dependence on tourism earnings; wage settlements; diversification of growth outside New Providence; job creation policies and operating efficiency of the public sector.
DC